Pengaruh Variasi Konsentrasi CN- Pada Proses Pelindian Bijih Au Terhadap Recovery Au, Gangue Ag, Cu dan Fe - Sutarno Sutarno; Andri Kabarubun; Iskandar Muda; R.M Ario Adisaputro (Jurnal Metalurgi dan Material Indonesia, 2019)
Gold is a precious metal, valuable, and widely found in Indonesia. Gold metal applications can be found in the jewelry, medical, catalyst and high-tech industries. In this study 35 mm of gold ore with a level of 15.6 ppm was extracted using NaCN as a lixiviant. The leaching process parameters included variations in 200, 300, and 400 ppm CN- concentrations, 48 hour leaching time and lixiviant pH in the range of 10-11. To increase the extraction rate was added Pb(NO3)2 catalyst and 15 ppm oxygen. Characterization results with AAS obtained the highest gold recovery was 88.46% Au at CN-300 ppm concentration, leaching time of 8 hours. In addition to gold metal, other metals are also found as gangue such as Ag, Cu and Fe.